ASSESSMENT OF ECONOMICALLY USEFUL TRAITS OF BEE BREED IN THE SOUTHERN OF KAZAKHSTAN - Shimelkova, R. Zh.; Aldiyarova, A. K.; Demidova, I. V.; Dosbolat, Zh. B.; Nuralieva, U. A. (ЗКАТУ им. Жангир хана, 2023)
Uncontrolled import of bee colonies leads to the metisation of bred breeds in our country. Breed testing of bees involves identifying the most promising breeds not only for the use of various sources of bribes, but also for accelerated development and increase in the number of families, and of course pollination of crops. To prevent the metisation of bees, researchers periodically monitor the breed composition and economically useful signs. It has been established that the growth rate of a bee family characterizes its winter hardiness and directly affects productivity. Based on this feature, queen bees with the highest egg production should be selected for breeding. More dynamic egg laying is observed in IE "Demidov" of the steppe zone averaged 919.6 pieces, and in IE "Gostinin" of the steppe zone, the egg production of queens is less by 2 pieces. The foothill and mountain zone lags behind the steppe zone by 14.6 eggs. The productivity of bee colonies also depends on the number of migrations to flowering honey plants. For example, when comparing the average honey productivity and wax productivity, variability is observed between stationary and nomadic content.
Shimelkova , R. Zh. ASSESSMENT OF ECONOMICALLY USEFUL TRAITS OF BEE BREED IN THE SOUTHERN OF KAZAKHSTAN / R. Zh. Shimelkova , A. K. Aldiyarova, I. V. Demidova , Zh. B. Dosbolat, U. A. Nuralieva. - Текст : непосредственный // Ғылым және білім=Наука и образование=Science and education. - 2023. - № 3-2 (72). Ч. ІІ. - Р. 214-222. - ISSN 2305-9397
Keywords: beekeeping; bee families; productivity; bee breed; evaluation; method; queen bee; drone; honey productivity; научной издание; зкату